A UTOPIA DA EMANCIPAÇÃO HUMANA NA COLÔMBIA: os sindicatos e os partidos de esquerda no período 2002-2010 - Duarte, Diana Ramírez (2014)
Reflection on the left parties and the unions in Colombia and their conditions and concrete possibilities of contributing to the emancipatory process in that country; thought in their specificity in the period 2002-2010, under the government of Álvaro Uribe Veléz (2002 -2010), but in reference with the resistance struggles and the left governments' election in Latin America. Under the guidance of the historical and dialectical materialism method, it was made the study of primary sources such as: the program of the Polo Democrático Alternativo that incorporates the proposals of the Colombian Communist Party; statutes of the General Confederation of Workers and of the Unitary Central of Workers; accusations and protests presented through the press. It is analyzed the relation of the subject with the armed insurgency and the social struggles that took place in Colombia during this period. It is concluded that there was an unity of the social struggles with the worker s unions and the Polo Democrático Alternativo to create a force of a concrete opposition against the government; that, moreover, in the perspective of the emancipation, it points for the need of overcoming the political polarization and the internal armed conflict, besides of contributing to strengthen the unity of the broader social base articulated with left-wing governments in Latin America.